The Influence of Mycorrhiza Application and Watering Intervals Under Drough Conditions on Vegetative Growth of Soybean (Glycine Max L. Merril.) - Timbul Hasonangan Sirait; Muhammad Idris; Khairunnisa Khairunnisa (BIOPENDIX, 2026)
Drought or dry season is an abiotic factor related to low availability of groundwater, which causes impaired plant growth. Water deficiency in plants will disrupt morphological and physiological activities, leading to halted growth. Mycorrhiza is a beneficial microorganism and a harmless symbiotic fungus that provides mutual benefits between soil-transmitted fungi and plant roots, helping in water and nutrient absorption. This study aims to determine the effect of mycorrhiza and the optimal watering level in overcoming drought stress in soybean plants (Glycine max L. Merril.). This study used a factorial Randomized Block Design consisting of 2 treatment factors with 3 replications. The first factor was mycorrhizal dosage with treatments M0 (0 g), M1 (15 g), M2 (25 g), M3 (35 g), and the second factor was the watering interval with treatments P0 (no watering), P1 (1 day), P2 (3 days), P3 (5 days). The study was conducted from January to February 2025. The results showed that the application of mycorrhizal fertilizer influenced the mitigation of drought stress on the vegetative growth of soybean plants. Meanwhile, the best watering treatment was P1 (1 day), which was able to increase the average leaf number parameter. Treatment P2 (3 days) was able to increase the average parameters of stomatal density and shoot dry weight. Treatment P3 (5 days) was able to increase the average parameters of root dry weight and shoot dry weight.